Alternative structure of new knowledge-based ergonomics risk assessment system - Fazilah, Abdul Aziz; Zakri, Ghazalli; N. M. Zuki, N. M. (2016)
This study is conducted to propose an alternative knowledge-based framework for assessing ergonomic risks. This knowledge-based framework is aimed at acquiring and quantifying work related risks of a musculoskeletal disorder associated with jobs that have high physical job demands and challenging working environments. Excessive physically demanding activities have been hypothesized as an active contributor to discomfort and muscle fatigue suffered by workers in automotive assembly plants. The objective of the knowledge acquisition process is to identify the risk iactors involved that include physical, psychological, individual and organizational categories. This proposed framework consists of the identification of the ergonomics risk factors phase, the development of knowledge based ergonomics assessment system (KBEAS) phase and finally, the prioritization of ergonomics risk factors phase. The analytical hierarchical process was employed to prioritize the ergonomics risk. This proposed framework is expected to help decision makers of the automotive industries to make an informed decision in predicting the ergonomics risks during the planning stage.